Pendampingan Strategi Pemasaran untuk Meningkatkan Daya Saing Produk Pertanian Organik (Kasus Kelompok Tani Jaya di Desa Ciaruteun Ilir) - Hana Salwa Muthmainnah; Nurul Amirah; Ardina Rahmi Yanti; Paru Ramadhan; Lintang Jayatalenta; Zessy Ardinal Barlan (Institut Pertanian Bogor, 2025)
Indonesia's potential resources are beneficial for both organic and inorganic agricultural businesses. The presence of organic farming can shift consumer consumption patterns, resulting in market competition with inorganic producers. Marketing in the farming sector plays a crucial role in ensuring that agricultural products reach the final consumer. This activity aims to assist farmers in developing effective marketing strategies for organic farm products to strengthen agrarian competitiveness. The method used is a qualitative approach through observation and in-depth interviews, as well as conducting action research with the stages of planning, acting, observing and reflecting. This activity was conducted at the Tani Jaya Group in Ciaruteun Ilir Village, Cibungbulang District, Bogor Regency. Data analysis uses the SWOT matrix to examine internal and external factors. The activity results show that the Tani Jaya Group has great potential in organic farming, but limited digital knowledge hinders its marketing. A branding strategy for marketing organic agricultural products to strengthen agricultural competitiveness through social media, complete product information, and the pre-order (PO) system is essential. Therefore, digital marketing assistance and professional social media management are also needed to increase farmers' awareness of marketing strategies as promotional media.